Toxic bile acids in gastro-oesophageal reflux disease: influence of gastric acidity. Issue 5 (1st May 1999) - Nehra, D; Howell, P; Williams, C P; Pye, J K; Beynon, J
Abstract : BACKGROUND: Bile acid toxicity has been shown in the gastric, colonic, and hepatic tissues; the effect on oesophageal mucosa is less well known. AIMS: To determine the spectrum of bile acids refluxing in patients with gastro-oesophageal reflux disease and its relation to oesophageal pH using a new technique of combined oesophageal aspiration and pH monitoring. METHODS: Ten asymptomatic subjects and 30 patients with symptoms of gastro-oesophageal reflux disease (minimal mucosal injury, erosive oesophagitis (grade 2 or 3 Savary-Miller), Barrett's oesophagus/stricture; n=10 in each group) underwent 15 hour continuous oesophageal aspiration with simultaneous pH monitoring. Bile acid assay of the oesophageal samples was performed using modified high performance liquid chromatography. RESULTS: The peak bile acid concentration and DeMeester acid scores were significantly higher in the patients with oesophagitis (median bile acid concentration 124 μmol/l; acid score 20.2) and Barrett's oesophagus/stricture (181 μmol/l; 43.3) than patients with minimal injury (14 μmol/l; 12.5) or controls (0 μmol/l; 11.1). The predominant bile acids detected were cholic, taurocholic, and glycocholic acids but there was a significantly greater proportion of secondary bile acids, deoxycholic and taurodeoxycholic acids, in patients with erosive oesophagitis and Barrett's oesophagus/stricture. Although bile acid reflux episodes occurred at variable pH, a temporal relation existed between reflux of taurine conjugates and oesophageal acid exposure ( r =0.58, p=0.009). CONCLUSION: Toxic secondary bile acid fractions have been detected in patients with extensive mucosal damage. Mixed reflux is more harmful than acid reflux alone with possible toxic synergism existing between the taurine conjugates and acid.